Optimal dietary lipid requirement of hybrid lemon fin barb (Barbonymus gonionotus ♀× Hypsibarbus wetmorei ♂) larvae - Weerasingha, Rochana; Kamarudin, Mohd Salleh; Abd Karim, Murni Marlina; Ismail, Mohammad Fadhil Syukri (Taylor and Francis, 2024)
Hybrid lemon fin barb is a crossed product between silver barb (Barbonymus gonionotus) and lemon fin barb (Hypsibarbus wetmorei). In the present study, the optimum dietary lipid requirement of larval hybrid lemon fin barb was examined using a total of 90 hybrid larvae (L) of 3-day-old (0.36 ± 0.01 mg). The larvae were stocked in triplicated 90 L tanks and fed with micro diets containing 0, 4, 8, 12, and 16% (FO 0, 4, 8, 12 and 16) dietary lipid levels for 20 days. While hybrid larvae fed non-lipid diet showed lowered survival and growth, larvae fed FO12 diet increased (p <.05) in weight gain, total length gain, specific growth rate, and protein efficiency ratio after 20 days. Hybrid larvae’s whole-body lipid content was increased with increasing dietary lipid level. Hybrid larvae consisted of significantly improved (p <.05) eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and n-3 fatty acid contents at 12% dietary lipid. Excessive dietary lipids resulted in lipid droplets in enterocytes and swollen hepatocytes. The hybrid larvae fed non-lipid diet had shrunken hepatocytes. In conclusion, the optimum dietary lipid requirement for hybrid lemon fin barb larvae in terms of maximum growth is determined at 13.5% dietary fish oil by second-order polynomial analysis.